Sustainability Status of Peatland in Different Types of Land Use - Yustika, Rahmah Dewi; Tyasmoro, Setyono Yudo; Suratman, Suratman (AGRIVITA Journal of Agricultural Science, 2025)
Peatlands are fragile ecosystems, making any utilization susceptible to changes that can disrupt the balance of natural resources and the environment. Three critical aspects that play a significant role in preserving peatland ecosystems (ecological, economic, and social) must be carefully considered in peatland use. A study of biophysical data and peatland usage was conducted in Pelalawan District, Riau Province, Indonesia, followed by a quantitative analysis of sustainability using Multidimensional Scaling (MDS) with the support of modified Rapfish software, referred to as Rapid Appraisal for Peat (RapPeat). The study aimed to assess the sustainability level of various peatland land use types and identify leverage attributes for targeted interventions to improve sustainability status. The research findings suggest that the peatland areas are less sustainable across these three assessed dimensions. The ecological dimension was the most sustainable, followed by the economic and social dimensions. Rubber and oil palm plantation land use types are more sustainable than the other land use types. Improving peatland sustainability involves targeted actions on leverage attributes to facilitate more sustainable practices across all dimensions.